Hydatid Cyst of Urinary Tract: 11 Cases at a Single Center - Zargar-Shoshtari, Mohammadali; Shadpour, Pejman; Robat-Moradi, Nader; Moslemi, Mohammadkazem (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; h3 mso-style-unhide:no; mso-style-qformat:yes; mso-style-link:"Heading 3 Char"; mso-style-next:Normal; margin-top:12.0pt; margin-right:0cm; margin-bottom:3.0pt; margin-left:0cm; mso-pagination:widow-orphan; page-break-after:avoid; mso-outline-level:3; font-size:13.0pt; font-family:"Arial","sans-serif"; span.Heading3Char mso-style-name:"Heading 3 Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:"Heading 3"; mso-ansi-font-size:13.0pt; mso-bidi-font-size:13.0pt; font-family:"Arial","sans-serif"; mso-ascii-font-family:Arial; mso-hansi-font-family:Arial; mso-bidi-font-family:Arial; font-weight:bold; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: We retrospectively reviewed clinical records of 11 patients with hydatid cyst of the urinary tract admitted to our institution from 1998 to 2005. Materials and Methods: Hospital and follow-up records of 11 patients with hydatid cyst of the urinary tract were reviewed and data on the patientsâ€™ symptoms and signs at presentation, radiological findings, diagnostic tests, pathologic findings, and surgical outcomes were reviewed. Results: The chief complaint was flank pain in 7 patients (63.6%). Hydaturia was not seen in any of our patients. Ten patients had renal involvement and 1 had a retrovesical hydatid cyst. Eosinophilia was detected in 2 of 11 patients who were tested. A positive indirect hemagglutination test was seen in 4 of 7 patients and a positive Casoni test in 1 of 2. Intravenous urography revealed caliceal distortion in 6 patients (54.5%), caliectasis in 3 (27.3%), and nonfunctioning kidney in 2 (18.2%). Ultrasonography showed a complex cyst in all of the patients. Computed tomography demonstrated multivesicular cystic structure in 4 patients (36.4%), complex cyst in 4 (36.4%), and a simple cyst in 3 (27.3%). Definite diagnosis was made only after surgical operation. We performed nephrectomy in 2 patients (18.2%), partial nephrectomy in 2 (18.2%), cystectomy plus marsupialization in 5 (45.4%), and retrovesical surgery in 1 (9.1%). One patient refused surgical treatment. There was no perioperative major complication. Conclusion: Renal hydatidosis is a rare entity and the main challenge is preoperative diagnosis. Radiological and serologic studies, although indicative, cannot confirm the diagnosis, and only pathologic examination after surgical removal can confirm echinococcal infection.